СONCEPTUAL APPROACH TO LOGISTICS CENTER DEVELOPMENT - Борисова, І. Д. (Science-based technologies, 2013)
This study is aimed to consider the functioning of logistics centers that provide optimal use of transport and equipment, and the final distribution of goods to its destination. The key aspects of logistics centers pointing to their development and evolution are specified. Moreover, basic functional purpose of logistics centers is analyzed. It is determined that motivation of logistics centers development has a significant contribution to the territorial and economic development in the area of its activity, namely improving in terms of logistics, transportation and warehousing activities and also oversees transportation costs and increase the competitiveness of industrial products. Finally, the attractive conditions for transportation and logistics companies are characterized and grounded.